2021
DOI: 10.1111/coa.13726
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement and patient‐reported evaluation of the nasal airway: Is correlation dependent on symptoms or on nasal airflow?

Abstract: Background Evidence has shown that the sensation of nasal breathing is related to variations in nasal mucosa temperature produced by airflow. An appropriate nasal airflow is necessary for changing mucosal temperature. Therefore, the correlation between objective measurements of nasal airflow and patient‐reported evaluation of nasal breathing should be dependent on the level of nasal airflow. Objectives To find if the correlation between patient‐reported assessment of nasal breathing and objective measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(154 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, there was no significant difference in the pre-operative PNIF value between these 2 groups (Table 2). This finding confirms the lack of relevant correlation between nasal airflow and patient-reported assessment of nasal breathing demonstrated by several studies [21][22][23][24][25][26][27][28][29] and is probably related to the multifactorial nature of nasal breathing sensation, which is related to but not solely dependent on nasal airflow. It has been demonstrated that low airflow prevents the sensation of suitable nasal breathing, 27 but patients with and without sensation of suitable nasal breathing may have similar levels of airflow.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, there was no significant difference in the pre-operative PNIF value between these 2 groups (Table 2). This finding confirms the lack of relevant correlation between nasal airflow and patient-reported assessment of nasal breathing demonstrated by several studies [21][22][23][24][25][26][27][28][29] and is probably related to the multifactorial nature of nasal breathing sensation, which is related to but not solely dependent on nasal airflow. It has been demonstrated that low airflow prevents the sensation of suitable nasal breathing, 27 but patients with and without sensation of suitable nasal breathing may have similar levels of airflow.…”
Section: Discussionsupporting
confidence: 89%
“…[36][37][38] Other studies have found correlation between nasal resistance and patient-reported measurements only in patients with nasal obstruction, [39][40][41][42][43][44] whereas other studies could not find correlation not even in symptomatic patients. [45][46][47][48] This lack of consistent correlation between objective measurements and patient-reported evaluation of nasal breathing suggests that factors other than the nasal airflow or nasal airway resistance are important for determining the subjective sensation of nasal breathing. There is evidence that the sensation of nasal breathing is mostly related to temperature variations caused by the cooling effect of the airstream on the mucosa of the nasal airway.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the lack of correlation many times demonstrated between measurements of these variables and subjective appreciation of nasal breathing. 48,[60][61][62][63][64] Nevertheless, an appropriate nasal airflow is required to produce changes in the nasal mucosal temperature and to provoke shear stress in the walls of the nasal cavity, as to trigger stimulation of both the thermoreceptors and the mechanoreceptors. Bailey et al found a negative correlation between nasal resistance and the degree of mucosal cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 However, another study by Xavier et al from 2021 examined the relationship between NOSE scores and PNIF values and demonstrated only a weak correlation between scores, further emphasizing the difficulty correlating objective findings to subjective results. 42 A limitation of this technique, similar to some of the previously mentioned instruments, is the variability in results based on mucosal congestion and the physiologic nasal cycle, and can fail to detect up to 25% of symptomatic patients with functionally relevant nasal structural deformities. 43 Still, a more recent prospective study by Fuller et al examining 136 patients, acknowledged the limitation between PNIF and subjective measures as a diagnostic tool, but did suggest utility on an individual scale to determine objective improvements following surgery.…”
Section: Peak Nasal Inspiratory Flowmentioning
confidence: 99%